EDITORIAL - Andrei, Vasile Liviu (Arena-Journal of Physical Activities, 2015)
Motto: â€œThe only thing that stands between a man and what he wants from life is often merely the will to try it and the faith to believe that it is possible.â€ (Richard M. DeVos-owner of the Orlando Magic NBA)